Automated, High‐Throughput Phenotypic Screening and Analysis Platform to Study Pre‐ and Post‐Implantation Morphogenesis in Stem Cell‐Derived Embryo‐Like Structures - Vinidhra Shankar; Clemens vanBlitterswijk; Erik Vrij; Stefan Giselbrecht (Advanced Science, 2024)
Abstract Combining high‐throughput generation and high‐content imaging of embryo models will enable large‐scale screening assays in the fields of (embryo) toxicity, drug development, embryogenesis, and reproductive medicine. This study shows the continuous culture and in situ (i.e., in microwell) imaging‐based readout of a 3D stem cell‐based model of peri‐implantation epiblast (Epi)/extraembryonic endoderm (XEn) development with an expanded pro‐amniotic cavity (PAC) (E3.5 E5.5), namely XEn/EPiCs. Automated image analysis and supervised machine learning permit the identification of embryonic morphogenesis, tissue compartmentalization, cell differentiation, and consecutive classification. Screens with signaling pathway modulators at different time windows provide spatiotemporal information on their phenotypic effect on developmental processes leading to the formation of XEn/EPiCs. Exposure of the biological model in the microwell platform to pathway modulators at two time windows, namely 0–72 h and 48–120 h, show that Wnt and Fgf/MAPK pathway modulators affect Epi differentiation and its polarization, while modulation of BMP and Tgfβ/Nodal pathway affects XEn specification and epithelialization. Further, their collective role is identified in the timing of the formation and expansion of PAC. The newly developed, scalable culture and analysis platform, thereby, provides a unique opportunity to quantitatively and systematically study effects of pathway modulators on early embryonic development.